Analytical Review on Improving Coconut Production and Management Practices in Fiji - Shirlyn Vandana Lata; Tamara Osborne-Naikatini (International Journal of Agronomy)
Coconuts are popularly regarded as the “Tree of Heaven” because of its multitude of uses from food, medicine, cosmetics, fuel, drink, oil, timber, domestic utensils, and cultural significance. Secondary data (published literature and FAOSTAT database) and firsthand data (limited to Fiji Islands) from an exploratory study by Lata et al., 2024, were used to assess coconut farming practices. In the past, the coconut sector particularly coconut oil and copra production were lauded for its export revenue and sectoral development in Pacific Island countries. However, price fluctuations, incidence of pest and disease, climate change impacts, senile palms, and transportation are among the long-term challenges in coconut production that have created setbacks and are currently limiting factors for the coconut industry and the economy. Fiji is an island nation in the South Pacific Ocean that account for 87% of the coconut population. Fiji’s exclusion in the global coconut market is a drawback to revitalizing the industry and marketing of coconut activity. One of the challenges foreseen is the breeding of Fiji Tall and Fiji Dwarf varieties only that limits genetic variability of coconut populations in Fiji. The coconut value chain is complex associating various players (farmers, processors, exporters, wholesalers, retailers, and consumers) to perform multiple functions to strengthen value-adding products and projected competition in the global market. The findings emphasize potential improvements in the coconut farming practices in Fiji through the integration of research development, financial security, and an analysis of the value chain. Therefore, this research contributes to an understanding of genetic variation within the Fiji coconut industry, which is necessary for adopting effective conservation strategies, germplasm utilization, and management of the coconut populations. This paper outlines actionable recommendations for effective coconut farming, particularly identifying gaps for conserving the rich diversity of coconut varieties in Fiji.